2019
DOI: 10.1016/j.ijcha.2019.100415
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with anemia and renal dysfunction in hospitalized heart failure with preserved ejection fraction (from the CN-HF registry)

Abstract: Background Although a large number of studies on heart failure with reduced ejection fraction (HFrEF) have found that anemia and renal dysfunction (RD) independently predicted poor outcomes, there are still few reports on patients with heart failure with preserved ejection fraction (HFpEF). Methods Clinical data of HFpEF patients registered in the China National Heart Failure Registration Study (CN-HF) were evaluated and the clinical features of patients with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 34 publications
(41 reference statements)
0
23
1
Order By: Relevance
“…In the included studies, three studies defined that their patients suffered from acute HF ( 31 , 32 , 44 ) and one had reported that they included cases with both acute and chronic HF ( 26 ). The rest of the seven studies did not provide details concerning the nature of the HF cases they included ( 23 26 , 30 , 41 , 42 ). Besides, five of the included studies had also reported the ejection fraction values for their sample ( 23 , 30 , 32 , 41 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the included studies, three studies defined that their patients suffered from acute HF ( 31 , 32 , 44 ) and one had reported that they included cases with both acute and chronic HF ( 26 ). The rest of the seven studies did not provide details concerning the nature of the HF cases they included ( 23 26 , 30 , 41 , 42 ). Besides, five of the included studies had also reported the ejection fraction values for their sample ( 23 , 30 , 32 , 41 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the seven studies did not provide details concerning the nature of the HF cases they included ( 23 26 , 30 , 41 , 42 ). Besides, five of the included studies had also reported the ejection fraction values for their sample ( 23 , 30 , 32 , 41 , 42 ). The average ejection fraction for all the included studies was found to be 47.5 ± 15.2% for the HF patients with anemia, and 44.9 ± 15.6% for the HF patients without anemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies are very heterogeneous, the results have always been consistent and similar to those of the present study. [15][16][17][18][19][20][21][22][23] The differences which make our study of interest are the large sample size analysed, and that it is the first study to include all patients consulting for AHF in ED, since other studies only included patients who were hospitalised or were outpatients. We believe this circumstance to be important since up to one-quarter of the patients with AHF do not require admission and are usually excluded from this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies including AHF episodes only analyse hospitalised patients. [15][16][17][18][19][20][21][22][23] The objective of this study was to analyse the differential characteristics of patients with AHF presenting criteria of CRAS at arrival at the hospital emergency department (ED) and the impact RD and anaemia have, individually and in combination in patients with CRAS, on the short-term events during the episode of decompensation.…”
Section: Introductionmentioning
confidence: 99%